The Ability of Resveratrol to Attenuate Ovalbumin-Mediated Allergic Asthma Is Associated With Changes in Microbiota Involving the Gut-Lung Axis, Enhanced Barrier Function and Decreased Inflammation in the Lungs - Alharris, Esraah; Mohammed, Amira; Alghetaa, Hasan; Zhou, Juhua; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Immunology, 2022)
Asthma is a chronic respiratory disease highly prevalent worldwide. Recent studies have suggested a role for microbiome-associated gut–lung axis in asthma development. In the current study, we investigated if Resveratrol (RES), a plant-based polyphenol, can attenuate ovalbumin (OVA)-induced murine allergic asthma, and if so, the role of microbiome in the gut–lung axis in this process. We found that RES attenuated allergic asthma with significant improvements in pulmonary functions in OVA-exposed mice when tested using plethysmography for frequency (F), mean volume (MV), specific airway resistance (sRaw), and delay time(dT). RES treatment also suppressed inflammatory cytokines in the lungs. RES modulated lung microbiota and caused an abundance of Akkermansia muciniphila accompanied by a reduction of LPS biosynthesis in OVA-treated mice. Furthermore, RES also altered gut microbiota and induced enrichment of Bacteroides acidifaciens significantly in the colon accompanied by an increase in butyric acid concentration in the colonic contents from OVA-treated mice. Additionally, RES caused significant increases in tight junction proteins and decreased mucin (Muc5ac) in the pulmonary epithelium of OVA-treated mice. Our results demonstrated that RES may attenuate asthma by inducing beneficial microbiota in the gut-lung axis and through the promotion of normal barrier functions of the lung.